New Liodessus species from the high Andes of Peru (Coleoptera: Dytiscidae, Bidessini) - Balke, Michael; Megna, Yoandri S.; Zenteno, Nilver; Figueroa, Luis; Hendrich, Lars (Zootaxa, 2020)
We describe four new species of the diving beetle genus Liodessus Guignot from the high Andean regions of Peru: Liodessus alpinus sp. nov. from Junín, L. hauthi sp. nov. from Huánuco and Churubamba, L. rhigos sp. nov. from Junín, and L. thespesios sp. nov. from Cusco. We delineate the species using morphological structures and provide a 5’ mitochondrial cytochrome c oxidase 1 database on the Barcode of Life Data System (BOLD). We also provide taxonomic notes on Liodessus acollensis Guignot, 1955 and L. andinus Guignot, 1957, described from the high Andes of Peru and Bolivia. These species occur at higher altitudes above 3,400 m and up to 4,900 m, and were collected in shallow, exposed peatland pools and puddles, mostly in steppes and high Andean Puna. The known distribution and habitat preferences of each species are outlined briefly.